SOCIAL-PSYCHOLOGICAL ASPECTS OF WORKING WITH UNIVERSITY ENTRANTS IN HIGHER EDUCATIONAL INSTITUTIONS - T. Borisova (Publishing House of the State University of Management, 2017)
Organizational and socio-psychological aspects of work with university entrants are considered. The phenomenon of cognitive dissonance, connected with the problem of choosing a university, is being considered and social and psychological recommendations for overcoming this phenomenon in work with applicants are offered.